Caries risk prognosis criteria in children with enamel hypoplasia of the permanent teeth, taking into account anthropogenic environmental factors - Liubarets, S.F.; Antomonov, M.Yu. (Environment & Health, 2018)
The hard dental tissue lesions, enamel hypoplasia in particular, represent a significant problem within the broad range of dental pathologies. The most common hypoplasia complication is dental caries. Study objective: to increase the efficiency of predicting caries as a complication in children with permanent teeth enamel hypoplasia based on regression analysis taking into account the influence of negative environmental factors. Materials and methods. The study object is enamel hypoplasia and carious lesions of permanent teeth. The study subject is the clinical and biochemical characteristics of hard dental tissues. Results. The prevalence of enamel hypoplasia of permanent teeth and its complications in 2024 children - residents of five regions of Ukraine referred to various health groups were analyzed. The prevalence of dental caries as a complication of systemic enamel hypoplasia (SEH) was analyzed depending on the respondents age, health group and harmful environmental factors, ionizing radiation in particular. In order to study the influence of various factors on the dental caries as a complication of SEH, a regression analysis was applied, the model was adequate (F = 83.35, p < 0.001). Hygienic oral pattern makes the most important contribution to the development of dental caries (Green-Vermillion index = 39.10 %). Conclusions. 1. Based on the selected criteria of hygienic oral pattern (Green-Vermillion index) and teeth enamel resistance (enamel resistance test, phosphate content in intact enamel and oral fluid), a regression linear model was created to predict the probability of caries as a complication in children of different age groups with permanent teeth enamel hypoplasia. 2. The created regression linear model can be recommended for implementation in the practice of medical institutions of Ukraine to optimize the dental monitoring in children of different age groups including the inhabitants of territories contaminated with radionuclides after the Chornobyl accident.